On solutions of matrix initial value problems by using differential transform method and convolution - Altun, Omer; Kilicman, Adem (AIP Publishing LLC, 2013)
In this study, we consider to solve some non-linear second order matrix initial value problems and boundary value problems in matrix forms with convolution by using differential transformation method. All calculations are implemented by Maple. The results are compared very well with those obtained by other analytical or.